2018
DOI: 10.1111/pace.13368
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation and left atrial thrombi resolution in nonrheumatic atrial fibrillation or flutter: A systematic review and meta‐analysis

Abstract: Warfarin is the most studied initial OAC agent for treating LAT in nonrheumatic AF and/or AFL with a resolution rate of nearly 80%. Further studies in DOACs are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…A recent systematic review published by our group yielded 17 vitamin K antagonist (VKA) studies and only two NOAC studies. 8 Warfarin studies with low risk of bias demonstrated an estimated 79.3% LA thrombus resolution rate after 3 weeks or more. Equivalency between warfarin and NOACs in this clinical scenario should not be assumed given few NOAC studies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review published by our group yielded 17 vitamin K antagonist (VKA) studies and only two NOAC studies. 8 Warfarin studies with low risk of bias demonstrated an estimated 79.3% LA thrombus resolution rate after 3 weeks or more. Equivalency between warfarin and NOACs in this clinical scenario should not be assumed given few NOAC studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent issue of Pacing and Clinical Electrophysiology , Wang et al . report a systematic review and meta‐analysis on LAT resolution with OACs.…”
Section: Current Management Of Af Patients With Latmentioning
confidence: 99%
“…We feel it is important to emphasize the utility of our study in the larger context of OAC agent selection for this clinical scenario. Warfarin, with a LA thrombus resolution rate of approximately 80%, is currently the only OAC agent approved by the United States Food and Drug Administration (FDA) for “treatment of the thromboembolic complications associated with atrial fibrillation.” NOAC selection for treatment of LA thrombus is off‐label and, in OAC naïve patients, chosen over an OAC agent that is both FDA approved and has fairly robust efficacy and effectiveness data. Off‐label drug use, while often reasonable, is not without risk and may bear legal consequences Neither the 2014 guideline for the management of patients with AF nor the 2019 focused update issued by the American Heart Association, American College of Cardiology, and Heart Rhythm Society specify the type of OAC agent that is preferred for treatment of LA thrombus when detected by TEE prior to consideration for cardioversion…”
mentioning
confidence: 99%
“…Retrospective cohort studies are important to build the “pyramid of evidence,” given few NOAC studies . It is our anticipation that multicenter randomized controlled trials and prospective cohort studies will ultimately address whether NOACs are reasonable, or perhaps even preferable, alternatives to warfarin for treatment of LA thrombus in nonvalvular AF or flutter.…”
mentioning
confidence: 99%
See 1 more Smart Citation